Poisoning Patterns Before, During, and after the COVID-19 Pandemic in the Poisoning Centers in Urmia: A Six-Year Retrospective Study - Majidi, Mohammad; Bazzaz, Zahra (International Journal of Medical Toxicology and Forensic Medicine, 2026)
Background: Poisoning is one of the main causes of emergency admissions and deaths worldwide, which could be affected by the COVID-19 pandemic. This study aimed to assess poisoning patterns before, during, and after the COVID-19 pandemic at poisoning centers in Urmia. Methods: In this retrospective, descriptive-analytical study, all poisoned patients hospitalized in Urmia poisoning centers from 2018 to 2023 were studied. Patients were categorized into groups before, during, and after the COVID-19 pandemic. Then, statistical analyses were performed using SPSS version 21. Results: This investigation evaluated 13197 patients (51.7% males, 48.3% females). The mortality rate was 323 (2.45% total; 75.9% males; 24.1% females). The patients' Mean± standard deviation age was (28 ± 14.05) years (min=14, max=96). Most patients were aged 21-30 years, and approximately half were male. The number of hospitalizations during the COVID-19 pandemic (2,665) decreased significantly compared with before (5,697) and after (4,835). Pesticide (41.1%), Pharmaceuticals (20.6%), Substance abuse (17.8%), Mixed poisonings (12.2%), and Alcohol (6.5%) were the most common causes of death during the COVID-19 pandemic, respectively. Mortality among males was higher than among females at all times. But the mortality rate during the COVID-19 pandemic (4%) increased significantly compared to before (1.7%) and after (2.5%). Significant relationships were detected between the patients' outcomes and age>60 years, Male, Widowed status, Higher (Academic) education, and Alcohol poisoning, Gases, Pesticides, Bites, and Foods/Mushrooms. Conclusion: Despite a decline in hospitalizations due to fears of COVID-19, it was able to change patterns of poisoning and mortality. Therefore, education to prevent pesticides, Alcohol, and drugs during public health crises can reduce morbidity and mortality.